2022
DOI: 10.3390/biology11111686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term High Temperature on Gas Exchange in Kiwifruits (Actinidia spp.)

Abstract: Climate changes occurring today require detailed research of the effects of increasing temperatures on photosynthesis in different species and cultivars. Temperature variability is a crucial determinant of the yield and quality of plants, particularly when high-temperature episodes coincide with their growth and fruit development. The effect of high temperature (HT) on higher plants primarily concerns photosynthetic functions, but the sensitivity of photosynthesis to high temperature is not well-understood in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…During the 2019-2020 and 2020-2021 study periods at two locations, the morphological, and physiological parameters of different kiwifruit varieties varied, but the differences were minor as compared to those differences that were observed for phenology. Similar results were reported by Li et al [122], who concluded that hightemperature resistance varieties should be used in the future to have good morphological and physiological traits. Furthermore, Zhong et al [123] explored the growth and physiological responses of four kiwifruit genotypes to salt stress and evaluated the tolerance using PCA.…”
Section: Temperature and Variety Affect Kiwifruit Morphology And Phys...supporting
confidence: 89%
“…During the 2019-2020 and 2020-2021 study periods at two locations, the morphological, and physiological parameters of different kiwifruit varieties varied, but the differences were minor as compared to those differences that were observed for phenology. Similar results were reported by Li et al [122], who concluded that hightemperature resistance varieties should be used in the future to have good morphological and physiological traits. Furthermore, Zhong et al [123] explored the growth and physiological responses of four kiwifruit genotypes to salt stress and evaluated the tolerance using PCA.…”
Section: Temperature and Variety Affect Kiwifruit Morphology And Phys...supporting
confidence: 89%
“…Under high-temperature stress, plants reduce the leaf temperature by regulating the transpiration rate (Tr) and stomatal characteristics [13], while stomatal opening is positively correlated with Gs and Tr [14]. Plants exhibit avoidance or acclimation mechanisms under short-term high-temperature conditions [15], and the Tr, stomatal opening, and Gs increase with increasing temperature [16]. Under long-term high-temperature conditions, plants prevent excessive water loss by reducing stomatal opening or even closing the stomata, resulting in reduced leaf water potential, Tr, and Pn [17,18] and thus protecting plants from high-temperature stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, the degree of HT-stress-induced reduction varied among different cultivars; thus, it is important to understand the physiological and molecular regulation of photosynthesis under HT stress. In a study, Li and his colleagues examined the physiological basis of HT-stress-induced reduction in photosynthesis in kiwifruit [ 10 ]. They found that a temperature exceeding 44.5 °C was detrimental to kiwifruits; nonetheless, kiwifruit cultivars with different ploidy levels (diploid and hexaploid) were found to be sensitive to HT stress, while tetraploids showed relatively higher HT tolerance, suggesting a positive correlation between polyploidy and variation in HT-induced reduction in photosynthesis [ 10 ].…”
mentioning
confidence: 99%